A competitive enzyme immunoassay for the quantitative detection of cocaine from banknotes and latent fingermarks. (May 2015) - van der Heide, Susan; Garcia Calavia, Paula; Hardwick, Sheila; Hudson, Simon; Wolff, Kim; Russell, David A.
Highlights: A sensitive and versatile competitive enzyme immunoassay (cEIA) has been developed. Quantitative detection of cocaine from both paper currency and latent fingermarks. The LOD of 0.162 ng mL −1 compares favourably to that of conventional techniques. Results from the fingermarks were compared to oral fluid samples. Endogeneously excreted cocaine can be quantified from a single latent fingermark. Abstract: A sensitive and versatile competitive enzyme immunoassay (cEIA) has been developed for the quantitative detection of cocaine in complex forensic samples. Polyclonal anti-cocaine antibody was purified from serum and deposited onto microtiter plates. The concentration of the cocaine antibody adsorbed onto the plates, and the dilution of the cocaine-HRP hapten were both studied to achieve an optimised immunoassay. The method was successfully used to quantify cocaine in extracts taken from both paper currency and latent fingermarks. The limit of detection (LOD) of 0.162 ng mL −1 achieved with the assay compares favourably to that of conventional chromatography–mass spectroscopy techniques, with an appropriate sensitivity for the quantification of cocaine at the low concentrations present in some forensic samples. The cEIA was directly compared to LC–MS for the analysis of ten UK banknote samples. The results obtained from both techniques were statistically similar, suggesting that the immunoassay was unaffected by cross-reactivity with potentially interfering compounds. The cEIA was used also for the detection of cocaine in extracts from latent fingermarks. The results obtained were compared to the cocaine concentrations detected in oral fluid sampled from the same individual. Using the cEIA, we have shown, for the first time, that endogeneously excreted cocaine can be detected and quantified from a single latent fingermark. Additionally, it has been shown that the presence of cocaine, at similar concentrations, in more than one latent fingermark from the same individual can be linked with those concentrations found in oral fluid. These results show that detection of drugs in latent fingermarks could directly indicate whether an individual has consumed the drug. The specificity and feasibility of measuring low concentrations of cocaine in complex forensic samples demonstrate the effectiveness and robustness of the assay. The immunoassay presents a simple and cost-effective alternative to the current mass spectrometry based techniques for the quantitation of cocaine at forensically significant concentrations.